The Security Versus Freedom Dilemma. An Empirical Study of the Spanish Case - Herranz de Rafael, Gonzalo; Fernández-Prados, Juan S. (Frontiers in Sociology, 2022)
One of the classic debates in public opinion, now more prevalent due to the COVID-19 pandemic, has been the dilemma between freedom and security. Following a theoretical review, this article sets out to establish the sociodemographic profiles and those variables that can correlate and/or explain the inclination towards one or the other, that is, the dependent variable "freedom-security," such as victimization or the assessment of surveillance. The analysis is based on the results of a survey prepared by the Center for Sociological Research (CIS, in Spanish) and administered to a sample of 5,920 Spaniards. The conclusions indicate that the majority inclination is for security, especially among older men, with elementary education attainment level and right-wing ideology. Furthermore, although victimization correlated with the dependent variable, the perception of being a possible victim led to a preference for safety rather than the actual experience of having been a victim. Finally, the positive assessment of surveillance through technologies such as video cameras explains or is strongly associated with security, making it a promising line of research for future work and a means to improve the understanding of the analyzed dilemma.